Volatile profiles from over-ripe purée of Thai mango varieties and their physiochemical properties during heat processing. - Malaiporn Wongkaew; Jiraporn Sangta; Sunee Chansakaow; Kittisak Jantanasakulwong; Pornchai Rachtanapun; Sarana Rose Sommano (PLoS ONE)
This research investigated volatile profiles of over-ripe Thai mango purée during thermal processing by solid-phase extraction, volatile quantification by XAD-2-solvent extraction, as well as descriptive sensory analysis. Overripe fruits of three varieties were analyzed for the ripening stage using specific gravity as well as firmness and the physiochemical properties were also reported. We found that aromatic profiles could be used as true representative to describe Thai mango identities of each varieties. A simple and straightforward heat treatment had differing effects on aroma characteristics and those effects were dependent with mango varieties. Indeed, the amount of terpene hydrocarbons and oxygenated sesquiterpenoids alternated after heat treatment. All descriptive attributes of heated 'sam-pee' purée were intensified while, heat treatment significantly improved only "mango identity" in 'maha-chanok' and "fermented" odour in 'keaw' purée. With or without heat treatment, the volatile profiles of 'maha-chanok' remained quite stable while heating played a significant role on chemical ingredients of 'keaw' and 'sam-pee'. Our study demonstrated that the manufacturing of the over-ripe mango into the products of high market value, selection of varieties is vitally important based upon their specific aroma characteristics before and after processing.